Small pituitary volume and central nervous system anomalies in Fanconi Anemia - Corredor, Beatriz; Solís, Inés; Zubicaray, Josune; Sevilla, Julián; Argente, Jesús (Frontiers in Endocrinology, 2024)
Introduction: Fanconi anemia (FA) is a genomic instability disorder associated with congenital abnormalities, including short stature and the presence of central nervous system anomalies, especially in the hypothalamic-pituitary area. Thus, differences in pituitary size could associate with the short stature observed in these patients. Our aim was to evaluate whether central nervous system abnormalities and pituitary gland volume correlate with height and hormone deficiencies in these patients. Methods: In this cross-sectional exploratory study 21 patients diagnosed with FA between 2017 and 2022 in a Spanish Reference Center were investigated. Magnetic resonance imaging (MRI) was performed and pituitary volume calculated and corelated with height and other endocrine parameters. Results: The percentage of abnormalities in our series was 81%, with a small pituitary (pituitary volume less than 1 SD) being the most frequent, followed by Chiari malformation type 1. The median value of pituitary volume was -1.03 SD (IQR: -1.56, -0.36). Short stature was found in 66.7% (CI95% 43-85.4). Total volume (mm 3) increases significantly with age and in pubertal stages. There were no differences between volume SD and pubertal stage, or the presence of endocrine deficiencies. No correlations were found between pituitary volume and the presence of short stature. The intraclass correlation index (ICC) average for volume was 0.85 (CI95% 0.61-0.94) indicating a good-to-excellent correlation of measurements. Discussion: Central nervous system anomalies are part of the FA phenotype, the most frequent after pituitary hypoplasia being posterior fossa abnormalities, which may have clinical repercussions in the patient. It is therefore necessary to identify those who could be candidates for neurosurgical intervention. The size of the pituitary gland is smaller in these patients, but this does not seem to be related to hormone deficiency and short stature or exposure to a low dose of total body radiation.